1997
DOI: 10.1097/00002030-199707000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid preventive therapy for tuberculosis in HIV-1-infected adults

Abstract: Overall there was no statistically significant protective effect of daily isoniazid for 6 months in the prevention of tuberculosis. In the TST-positive subjects, where reactivation is likely to be the more important pathogenetic mechanism, there was some protection and some reduction in mortality, although this was not statistically significant. The small number of individuals in this subgroup made the power to detect a statistically significant difference in this subgroup low. Other influences that may have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
1
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 9 publications
4
98
1
3
Order By: Relevance
“…Out of 14 trials identified in the Cochrane review, two studies met our criteria (4,5). The Medline search identified 954 papers, from which 15 reported results from prospective studies on TB-preventive therapy, and one met our inclusion criteria (6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 14 trials identified in the Cochrane review, two studies met our criteria (4,5). The Medline search identified 954 papers, from which 15 reported results from prospective studies on TB-preventive therapy, and one met our inclusion criteria (6).…”
Section: Resultsmentioning
confidence: 99%
“…The effect is most clearly seen in individuals with presumed Mycobacterium tuberculosis infection, as indicated by a positive tuberculin skin test (TST) (2,3). However, long-term follow-up of TB-preventive therapy trials set in sub-Saharan Africa have shown high rates of TB post IPT (2,(4)(5)(6)(7)(8), and the results of the recently published Thibela study (9) showed a rapid loss of protection following completion of IPT. It is unclear what drives this lack of durable protection from TB disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas there is ample research evidence showing that PT reduces the individual risk of active tuberculosis in HIV-positive persons with LTBI [6][7][8], the impact of this intervention toward the public health problem of tuberculosis in contemporary sub-Saharan African populations has hitherto not been adequately analyzed. Our model-based analysis that took into consideration the high prevalence of tuberculosis and HIV infection in this region provides estimates of the likely effect size of PT on tuberculosis case rates in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample research evidence demonstrating that tuberculosis preventive therapy (PT) reduces the individual risk of active tuberculosis in HIV-positive persons believed to be latently infected with Mycobacterium tuberculosis [6][7][8]. In view of these findings, the World Health Organization (WHO), the Joint United Nations Programme on HIV/AIDS (UNAIDS), and the International Union Against Tuberculosis and Lung Disease (IUATLD) recommend PT for tuberculin skin test (TST)-positive, HIV-infected persons who do not have active tuberculosis [9,10].…”
Section: Introductionmentioning
confidence: 99%